2.45 GHz low level CW microwave radiation affects embryo implantation sites and single strand DNA damage in brain cells of mice, mus musculus - Singh V.P.; Singh P.; Chaturvedi C.M.; Shukla R.K.; Dhawan A.; Gangwar R.K.; Singh S.P. (My University, 2025)
To study the effect of microwave radiation on the early stages of pregnancy (implantation) and DNA damage in brain cells, female mice were exposed to 2.45 GHz electromagnetic field (EMF) for 2 hours/ day at power density of 0.1250 mW/cm2 for the period of 30 days (pre-mating period, 22 days; mating period, 5 days; post mating period, 3 days). The results indicate asymmetrical implantation in the two horns of the uterus in addition to alteration in embryo positioning and altered embryo spacing in exposed mice as compared to control. The microwave radiation also induced significant DNA break in brain cells. Our findings point towards microwave radiation induced adverse effects on early embryonic development (implantation) as well as increased DNA damage in brain cells, although further studies are required to understand the extent and the mechanism of these effects. In view of the increased use of microwaves in the modern society and MW induced pathogenesis reported earlier as well as in the present study, it is necessary to define the safer use and threshold limit of the non-ionizing radiation in terms of its biological effects.